COKELAT DAN PEREMPUAN (Analisis Wacana Kritis Sara Mills pada Iklan Televisi Tim-Tam dan Tango Crunch Cake) - Jojor Hanna Ruth Simanjuntak; Dewi Kartika Sari (Universitas Kristen Satya Wacana, 2014)
Advertisement is one kind of communication. An advertisement will have no meaning without a message in it. The message which is delivered by advertisement could be verbal, non-verbal, even both verbal and non-verbal. One of the interesting things in this research is two TV advertisements about snacks, such as chocolate layered snack. Tim-Tam and Tango Crunch Cake, they are showing verbal and even non-verbal message, in which woman as a signed object that finally constructing a woman.This research aims to analyze the woman’s position in Tim-Tan and Tango Crunch Cake advertisement. This research uses critical analysis from Sara Mills, one of the discourses which analyzes about feminist see how is the position of subject-object and the viewers on Tim-Tam and Tango Crunch Cake advertisement, then it will reveal the discourse which will be shown to public in order to know the woman’s construction and to explain the pattern of woman’s construction through some scenes on Tim-Tam and Tango Crunch Cake advertisement.The result of this research shows that Tim-Tam and Tango Crunch Cake advertisement still use woman’s construction as an object. Woman is still used as an object trough body and her position. Woman’s presence though acts as subject and object position, still does not make advertisement support the existence of women but the influence in patriarchy ideology, feminism theory, resulting woman construction such as, woman construction through body, construction as perfect being, construction in dresses, and construction as object complement. Keywords: Conctruction, Discourse Analysis, Feminism, Tim-Tam and Tango Crunch Cake advertisement.